Anna Maria Brodeau Thornton papers - Thornton, Anna Maria Brodeau, 1775?-1865.
Seven bound volumes containing diaries, journals, essays, log of household visitors, daily log of activities, household accounts, silhouettes of unidentified people, and other papers primarily describing social life in Washington, D.C., with extensive detail about housekeeping and expense matters. There are gaps in the diaries, with a major one occurring during the years 1816-1827.
Includes entries relating to the schedule and work of Thornton's husband, architect William Thornton, on the east elevation of the Capitol, correspondence with Thomas Jefferson, visits to President Jefferson's home, a smallpox outbreak, paving of Pennsylvania Avenue, the British invasion of Washington, D.C., in 1814, the gun explosion on the steamship Princeton in 1844, inauguration of President James K. Polk in 1845, return of land to Virginia from Washington, D.C., in 1846, trips to Virginia, North Carolina, and Newburyport, Massachusetts, and Thornton's years spent in Tortola, Virgin Islands. A collection of autographs includes signatures of Henry Clay, James Madison, and John Peter Van Ness.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Wife of architect William Thornton.
Collection material in English and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Clay, Henry, -- 1777-1852 -- Autographs; Jefferson, Thomas, -- 1743-1826.; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Madison, James, -- 1751-1836 -- Autographs; Polk, James K. -- 1795-1849 -- Inauguration, 1845.; Thornton, William, -- 1759-1828.; Van Ness, John Peter, -- 1770-1846 -- Autographs; Princeton (Steamship); United States Capitol (Washington, D.C.); Smallpox; Massachusetts -- Description and travel; Newburyport (Mass.) -- Description and travel; North Carolina -- Description and travel; Pennsylvania Avenue (Washington, D.C.); Tortola (British Virgin Islands) -- Social life and customs; United States -- History -- War of 1812 -- Campaigns; Virgin Islands -- Social life and customs; Virginia -- Boundaries -- Washington (D.C.); Virginia -- Description and travel; Washington (D.C.) -- Boundaries -- Virginia; Washington (D.C.) -- History -- Capture by the British, 1814.; Washington (D.C.) -- Social life and customs